2020
DOI: 10.1177/2324709620944091
|View full text |Cite
|
Sign up to set email alerts
|

Heparin-Induced Thrombocytopenia in COVID-19

Abstract: COVID-19 (coronavirus disease-2019) infection is a highly prothrombotic state, resulting from a dysregulation of the coagulation cascade. Therefore, thromboprophylaxis is strongly recommended in these patients, with some experts even advocating for therapeutic dosing to prevent thromboembolic events. Heparin-induced thrombocytopenia (HIT) is a well-known complication of heparin therapy. In this article, we report a case of HIT in a patient with COVID-19. A 63-year-old male presented with 1 week of dry cough an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
44
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(45 citation statements)
references
References 13 publications
0
44
0
1
Order By: Relevance
“…Curiously, several patients with COVID-19, meeting clinical diagnostic criteria for heparin-induced thrombocytopenia, subsequently tested positive for anti-PF4 antibodies, but in heparin-induced platelet aggregation assays were negative using the heparin-induced thrombocytopenia confirmatory test platelet serotonin release assay. 172 , 173 Most recently, it was revealed that circulating blood IgG in patients with COVID-19 promotes a procoagulant phenotype and thrombocytopenia through platelet apoptosis by stimulating platelet Fc gamma receptor IIA. 174 Overall, a pattern of autoantibody production in COVID-19 that simultaneously activates neutrophils and promotes thrombosis seems clear and may account for the morbidity and mortality benefit shown in the CoDEX and Recovery trials, respectively, when patients were randomized to immune suppression with dexamethasone.…”
Section: Indirect Myocardial Effectsmentioning
confidence: 99%
“…Curiously, several patients with COVID-19, meeting clinical diagnostic criteria for heparin-induced thrombocytopenia, subsequently tested positive for anti-PF4 antibodies, but in heparin-induced platelet aggregation assays were negative using the heparin-induced thrombocytopenia confirmatory test platelet serotonin release assay. 172 , 173 Most recently, it was revealed that circulating blood IgG in patients with COVID-19 promotes a procoagulant phenotype and thrombocytopenia through platelet apoptosis by stimulating platelet Fc gamma receptor IIA. 174 Overall, a pattern of autoantibody production in COVID-19 that simultaneously activates neutrophils and promotes thrombosis seems clear and may account for the morbidity and mortality benefit shown in the CoDEX and Recovery trials, respectively, when patients were randomized to immune suppression with dexamethasone.…”
Section: Indirect Myocardial Effectsmentioning
confidence: 99%
“…Paradoxically, HIT is characterized by both thrombocytopenia and a prothrombotic state. Recently, some reports presented the occurrence of HIT in COVID-19 patients [36,37]. However, larger investigations are warranted to confirm this increased incidence of HIT and to understand its physiopathology [36].…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…Several reports of HIT were reported (a total of 9 reports/series including 18 cases) before the current vaccine rollout; these were reviewed and summarized in table 1 (4)(5)(6)(7)(8)(9)(10)(11)(12). All the reports incriminated heparin in the development of the observed prothrombotic state.…”
Section: Resultsmentioning
confidence: 99%